A combined optogenetic-knockdown strategy reveals a major role of tomosyn in mossy fiber synaptic plasticity - Ben-Simon, Yoav (Cell Rep, 2015)
Neurotransmitter release probability (P(r)) largely determines the dynamic properties of synapses. While much is known on the role of presynaptic proteins in transmitter release, their specific contribution to synaptic plasticity is unclear. One such protein, tomosyn, is believed to reduce P(r) by interfering with the SNARE complex formation. Tomosyn is enriched at hippocampal mossy fiber-to-CA3 pyramidal cell synapses (MF-CA3), which characteristically exhibit low P(r), strong synaptic facilitation and pre-synaptic PKA-dependent LTP. To evaluate tomosyn's role in MF-CA3 function, we used a combined knockdown (KD)-optogenetic strategy whereby presynaptic neurons with reduced tomosyn levels were selectively activated by light. Using this approach in mouse hippocampal slices we found that facilitation, LTP, and PKA-induced potentiation were significantly impaired at tomosyn-deficient synapses. These findings not only indicate that tomosyn is a key regulator of MF-CA3 plasticity, but also highlight the power of a combined KD-optogenetic approach to determine the role of presynaptic proteins.